Padrões entoacionais e construção de sentido : um trabalho com gênero textual no 1º ano do ensino fundamental - Galindo, Talita Cruz (2011)
This research aims at investigating the intonational patterns in the construction of meaning in children's productions of the 1st year of elementary school, using different text genres. For this, we have investigated children who attend a private college of the City of Recife, aged between 6 and 7 years, both male and female. Data were collected during reading activities, where the teacher told stories to students using different kinds of texts, such as fable, fairy tale, comic book and letter. The research presents a qualitative analysis of the activity of reading, analyzing the role of intonation in the construction of meaning. Data analysis was performed on the model of Interactive Intonation by David Brazil (1985), seeking to identify the intonation clues provided in the teacher reading to his students and their relation to the construction of meaning. The results show that intonation takes three textual functions, organizational, informative and interactive, playing a significant role in the construction of meaning in reading activity, and that the proeminent words used by the teacher, were almost the same used by the students, helping to build the meaning in reading . The research contributed both to the development and improvement of the oral speech activity particularly as related to the intonational patterns to construct meaning, and providing a better textual production, but also to develop strategies that can reduce the difficulties in the oral production of children through the construction of moments of interaction between therapist and patient, promoting the development of the oral text by the child, giving a new meaning to reading